The tyrosine phosphatase Shp‐2 confers resistance to colonic inflammation by driving goblet cell function and crypt regeneration. Issue 1 (5th December 2018) - Gagné‐Sansfacon, Jessica; Langlois, Ariane; Langlois, Marie‐Josée; Coulombe, Geneviève; Tremblay, Sarah; Vaillancourt‐Lavigueur, Vanessa; Qu, Cheng‐Kui; Menendez, Alfredo; Rivard, Nathalie
Abstract: The Src homology‐2 domain‐containing tyrosine phosphatase 2 (SHP‐2) regulates many cellular processes, including proliferation, differentiation and survival. Polymorphisms in the gene encoding SHP‐2 are associated with an increased susceptibility to develop ulcerative colitis. We recently reported that intestinal epithelial cell (IEC)‐specific deletion of Shp‐2 in mice ( Shp‐2 IEC‐KO ) leads to chronic colitis and colitis‐associated cancer. This suggests that SHP‐2‐dependent signaling protects the colonic epithelium against inflammation and colitis‐associated cancer development. To verify this hypothesis, we generated mice expressing the Shp‐2 E76K activated form specifically in IEC. Our results showed that sustained Shp‐2 activation in IEC increased intestine and crypt length, correlating with increased cell proliferation and migration. Crypt regeneration capacity was also markedly enhanced, as revealed by ex vivo organoid culture. Shp‐2 activation alters the secretory cell lineage, as evidenced by increased goblet cell numbers and mucus secretion. Notably, these mice also demonstrated elevated ERK signaling in IEC and exhibited resistance against both chemical‐ and Citrobacter rodentium ‐induced colitis. In contrast, mice with IEC‐specific Shp‐2 deletion displayed reduced ERK signaling and rapidly developed chronic colitis. Remarkably, expression of an activated form of Braf in Shp‐2‐deficient mice restored ERK activation, goblet cell production and prevented colitis. Altogether, our results indicate that chronic activation of Shp‐2/ERK signaling in the colonic epithelium confers resistance to mucosal erosion and colitis. © 2018 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.